Optimization of Mitigation Communication in Addressing Earthquake Threats in Majene Regency: Local Wisdom Based Approach - Rezki Rahmawati; Dewi Nuraliah; Mussadad (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2026)
Majene Regency West Sulawesi has a very high level of earthquake vulnerability due to its position in an active subduction zone.This research identifies, analyzes and optimizes local wisdom-based earthquake mitigation communication using a qualitative ethnographic approach through in-depth interviews and participatory observation in five sub-districts.The results show that the Majene Regency Government faces limitations in formal mitigation communication due to budget and infrastructure constraints. However, the Mandar community developed a comprehensive mitigation communication system based on local wisdom: the terminology “linor” and “lino” for earthquakes, “lembo tallu” and “lembo pitu” for tsunamis, observation of natural signs as non-verbal communication, “banua kayyang” architecture as short communication, and the “tolak bala” ritual as spiritual communication. The communities implement this system in preparedness by using inherited knowledge for evacuation routes and verifying natural signs through BMKG information via smartphone.The Convergent Communication Model that integrates traditional communication with modern technology can be a solution to optimize mitigation communication to increase community preparedness.